(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Bronchiolitis is a common manifestation of lower respiratory tract infection in children under 9 months of age. So far, some clinical and diagnostic issues, in particular bronchiolitis caused by respiratory syncytial virus, have not been resolved. The article presents the results of studying the clinical, functional and immunological features of the course of acute bronchiolitis in children. The clinical presentation of bronchiolitis depends on the clinical form of the disease and the etiology of the disease, the main causative agent of which is the respiratory syncytial virus. The detected imbalance of the cytokine profile can be a sign of the severity of infectious bronchiolitis, which helps to determine the next tactics of patient treatment and improve clinical results.